2017
DOI: 10.1007/s11786-017-0301-9
|View full text |Cite
|
Sign up to set email alerts
|

Motion of a Swinging Atwood’s Machine: Simulation and Analysis with Mathematica

Abstract: A generalized model of the Atwood machine when one body is constrained to move along a vertical axis while the other one can swing in a plane is considered. Combining symbolic and numerical calculations, we have obtained equations of motion of the system and analyzed their solutions. We have shown that oscillation can completely modify a motion of the system while the simple Atwood machine demonstrates only the uniformly accelerated motion of the bodies. The validity of the results obtained is demonstrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…One of the areas of the variable-length pendulum is the Swinging Atwood's Machine (SAM). In this case, the pendulum's mass swings in a two-dimensional plane, producing a chaotic behavior without colliding with the other mass known as the counterweight [50][51][52]. The inextensible massless string suspended on two frictionless pulleys connects the two groups (see also [53]), as presented in Fig.…”
Section: A Variable-length Pendulum System: Swinging Atwood's Machinementioning
confidence: 99%
“…One of the areas of the variable-length pendulum is the Swinging Atwood's Machine (SAM). In this case, the pendulum's mass swings in a two-dimensional plane, producing a chaotic behavior without colliding with the other mass known as the counterweight [50][51][52]. The inextensible massless string suspended on two frictionless pulleys connects the two groups (see also [53]), as presented in Fig.…”
Section: A Variable-length Pendulum System: Swinging Atwood's Machinementioning
confidence: 99%
“…To clarify the physical reasons of such influence of oscillation on the system motion in the previous paper [10] we considered the simplest generalization of the Atwood machine when only one body is allowed to swing in a plane while the other body can move only along a vertical. We have shown that oscillation results in increasing of an averaged tension of the thread which depends on the amplitude of oscillation.…”
Section: A N Prokopenya (B)mentioning
confidence: 99%
“…In case of the two oscillating bodies the equations of motion (2.3)-(2.5) are much more complicated in comparison to the case of one body oscillation (see [10]). And to demonstrate some new peculiarities of the system motion we have to look for numerical solutions of these equations for different initial conditions and different values of the system parameter μ.…”
Section: Motion Of Atwood's Machine With Two Oscillating Bodiesmentioning
confidence: 99%
“…The investigation of the proposed scenario outlined in the abstract stems from questioning, "For two identical blocks which one reaches the vertical leg of the table first?" [1] [2]. Intuitively, it is an easy task without quantifying… Claim the block on the table!…”
Section: Motivation and Goalsmentioning
confidence: 99%